2010
DOI: 10.1021/cm102276a
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Helical Nanofibers Made of Achiral Molecular Disks Having Molecular Adapter

Abstract: An achiral disk-shaped molecule (2) having one imidazole unit was found to be assembled into long and twisted nanoscopic fibers having 10 - 100 nm width as shown by transmission electron microscopy (TEM) and atomic force microscope (AFM). Compound 2 leads to spontaneous chiral symmetry breaking through the steric effect of imidazole units during the formation of one-dimensional stacks. The imidazole in 2 acts as a molecular adaptor to form hydrogen bonds and accumulate metal ions. The supramolecular connection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 87 publications
4
38
0
Order By: Relevance
“…Similarly, when spectra are recorded for $ in CHCl 3 at increasing concentrations (1.0 µg mL 1 to 1.0 mg mL 1 ), λ max shifts from 379 to 384 nm (see supplementary information Figure S9). These results are consistent with observations on organogelating triphenylenes by Bai et al 21 , Kimura et al 26 and Munoz Resta et al 25 , but again contrast with those of Shinkai et al 45 who observed emission spectra similar to Fig. 6b for their triphenylene derivative in chloroform (no gel) but a large new emission peak above 500 nm, attributed to excimer emission, for their triphenylene in cyclohexane (gel).…”
Section: And $ Photographs Of the Heated Sols (Top)supporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, when spectra are recorded for $ in CHCl 3 at increasing concentrations (1.0 µg mL 1 to 1.0 mg mL 1 ), λ max shifts from 379 to 384 nm (see supplementary information Figure S9). These results are consistent with observations on organogelating triphenylenes by Bai et al 21 , Kimura et al 26 and Munoz Resta et al 25 , but again contrast with those of Shinkai et al 45 who observed emission spectra similar to Fig. 6b for their triphenylene derivative in chloroform (no gel) but a large new emission peak above 500 nm, attributed to excimer emission, for their triphenylene in cyclohexane (gel).…”
Section: And $ Photographs Of the Heated Sols (Top)supporting
confidence: 92%
“…The first of these was 2,3,6,7,10,11 hexa (1,4,7 trioxaoctyl) triphenylene (TP6EO2M), which forms hydrogels / lyotropic phases in water 13,14,15 . Subsequently several triphenylene derivatives have been reported which are capable of gelating organic solvents 6,16,17,18,19,20,21,22,23,24,25,26 , while others have been shown to form physical gels in combination with an additional gelator 27 . This reflects an increasing interest in low molecular weight organogelators (LMOGs) generally 28 , and π gelators in particular 29 , due to their manifold potential technological applications.…”
Section: ! "mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, spontaneous chiral symmetry breaking through the steric effect of imidazole upon gelation was achieved. 282 Another chiral supramolecular gel assembled by achiral molecules is also related to the complexation of the imidazole unit with metal ions. You and co-workers demonstrated that simple achiral molecules containing an imidazole unit could form supramolecular polymers by complexation with Ag + , which can further gel in a variety of solvents.…”
Section: Gel Systemsmentioning
confidence: 99%
“…[6] Thev ast majority of spontaneously resolving systems are found to occur in organic solvents where weak solvation energy is overcome by long-range intermolecular forces, [7] although there are examples of such phenomena in alcohol. [8] Arecent breakthrough in this field occurred when Janietz, Tschierske, and co-workers reported spontaneous symmetry breaking for as imple,a chiral, hydrogen-bonded N-heterocycle. [1b] They recognized the significance of this finding and speculated that the development of homochirality in biological systems could have occurred in similar heterocycles connected to ribose phosphate units.H erein, we report the discovery that spontaneously formed ribose-5-phosphate substituted N-heterocycles [9] self-assemble in aqueous solution to form macroscopic domains of homochiral structures.T his finding may provide aclue to the origin of homochirality in living systems.…”
mentioning
confidence: 99%